1974
DOI: 10.1159/000122301
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal-Gonadal Relations and Fertility: The Effects of Repeated Stress upon the Adrenal Rhythm

Abstract: We have previously reported that immobilization stress administered twice daily over a one-week period results in delayed puberty and reduced fertility in C57/B16 mice exposed to the stress prior to or at the onset of puberty. Exposure to the same stress in adult cycling or non-cycling females led to larger litter sizes and a greater incidence of conception. The purpose of the present study was to determine whether the effects of stress on fertility were associated with changes in the amplitude or rhythm of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1976
1976
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 8 publications
(10 reference statements)
0
4
0
1
Order By: Relevance
“…For instance, stress exposure during the peripubertal period increases the display of anxiety- and depression-like behavior in response to stress in adulthood (Tsoory et al, 2007), as well as interfere with daily rhythms of corticosterone secretion (Paris and Ramaley, 1974). Peripubertal exposure to stressors also has persistent effects on the hypothalamic-pituitary-gonadal axis.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, stress exposure during the peripubertal period increases the display of anxiety- and depression-like behavior in response to stress in adulthood (Tsoory et al, 2007), as well as interfere with daily rhythms of corticosterone secretion (Paris and Ramaley, 1974). Peripubertal exposure to stressors also has persistent effects on the hypothalamic-pituitary-gonadal axis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, basal levels of stress-related hormones differ between pubertal and adult mice (Goel and Bale, 2007; Laviola et al , 2002). Furthermore, female mice exposed to an immobilization stressor during puberty display a persistent shift in the peak, as well as loss of daily corticosterone secretion rhythm (Paris and Ramaley, 1974). Moreover, exposure to stressors, such as heat, immobilization, or ether, during the prepubertal period has long-term negative effects on the reproductive capacity of female mice (Paris and Ramaley, 1973).…”
mentioning
confidence: 99%
“…It has been shown that adrenal steroid fluctuations can interfere with ovulation and that fertility is reduced if there is no daily rhythm of serum corticosterone present (Ramaley, 1974;Paris & Ramaley, 1974). Ramaley (1975) states that the presence of an adrenal rhythm is usually associated with regular vaginal smear cycles.…”
Section: Discussionmentioning
confidence: 99%